Peran Motivasi Belajar Berpartisipasi Dalam Peningkatan Prestasi Peserta Didik Di SMK Azzainiyyah - Raudhatul Janah; Khoirunnisa Nurfadilah; Siti Qomariyah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
The importance of learning motivation is very influential on student learning achievement, both intrinsic and extrinsic motivation. This research was conducted at SMK Azzainiyyah Sukabumi Regency. The purpose of this study was to determine the role of learning motivation to participate in improving student achievement at SMK Azzainiyyah Sukabumi Regency. The research approach uses descriptive qualitative with field studies. Data collection techniques with interviews, observation, and documentation. The results of the study stated that the motivation to study at SMK Azzainiyyah had two factors; intrinsic and extrinsic motivation. Many achievements were achieved thanks to the motivation to learn, both cognitive, affective, and psychomotor achievements. Participatory learning motivation plays a role in improving student achievement, including: increasing student involvement, increasing conceptual understanding, increasing intrinsic motivation, encouraging creativity and initiative and building social skills.